(untitled) (Research, Society and Development, 2020)
Technologies have shown an increasingly high degree of importance in people’s lives, making it important to reflect on their use in education and the role of teachers and the methodologies currently used in the classroom. The use of pedagogical practices associated with new technologies, such as geotechnologies, bring students’ relations with them closer together, promoting more attractive and efficient learning. Thus, this research aims to evaluate the potential of geotechnologies used in the teaching of Geoprocessing in a Technical Course in Environment Integrated to Secondary Education at IFMG and how these could assist the other course subjects related to environmental study. For this, an empirical research was carried out through a qualitative approach with a group of ten Professors who teach twelve subjects in the referred Course. The Teachers answered a questionnaire with questions related to their previous knowledge regarding the geodidactic resources involved in the teaching of geoprocessing such as, GNSS, Remote Sensing and GIS, their training and experience, in addition to questions related to the teaching environment. The results obtained with this research lead us to conclude that the use of geotechnologies can optimize the teaching of disciplines related to environmental study. But for that, efforts are needed in order to train and provide theoretical and practical support to teachers for the use of such resources so that they can have security and reliability in the use of geotechnological resources.